2016
DOI: 10.22159/ajpcr.2016.v9i6.13961
|View full text |Cite
|
Sign up to set email alerts
|

Study of Multidrug Resistance Pattern among Escherichia coli isolated from patients with Urinary tract infection

Abstract: Objective: Urinary tract infections (UTIs) are some of the most common bacterial infections encountered in community and cause of significant morbidity and high medical cost. Escherichia coli is the most common pathogen responsible for the majority of UTI infections. Antimicrobial drugs have been routinely prescribed for the empirical treatment of UTIs which has led to a dramatic increase in antibiotic resistance pattern of E. coli. The aim of the present study was to analyze the multidrug resistance (MDR) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…[20] While other studies reported different results such as: in India they reported the highest rate(51.15%) of E. coli infection among females aged 21-40 years, while it was 53.84% among males aged 40 to 80 years. [16] Over all ages, the risk of UTI infection in females was higher than that of males. [42] This could be attributed to a variety of factors, such as; the anatomical structure of the urinary tract, sexual intercourse, personal hygiene and number of pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…[20] While other studies reported different results such as: in India they reported the highest rate(51.15%) of E. coli infection among females aged 21-40 years, while it was 53.84% among males aged 40 to 80 years. [16] Over all ages, the risk of UTI infection in females was higher than that of males. [42] This could be attributed to a variety of factors, such as; the anatomical structure of the urinary tract, sexual intercourse, personal hygiene and number of pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains in spreaded plated were allowed to grow for 18-24 hours at 37°C, aerobically. 24 The zones of inhibition around each disc were measured and compared with the zone diameter as per the standards of the clinical laboratory standards institute (CLSI) guidelines. 25 Escherichia coli 10974 was obtained from Deutsche Sammlung von Mikroorganismen und Zellkulturen GmbH (DSMZ), Germany.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 99%